A practical toolbox for the effective transition of adolescents and young adults with asthma and allergies: An EAACI position paper. Issue 1 (18th October 2022) - Vazquez‐Ortiz, Marta; Gore, Claudia; Alviani, Cherry; Angier, Elizabeth; Blumchen, Katharina; Comberiati, Pasquale; Duca, Bettina; DunnGalvin, Audrey; Garriga‐Baraut, Teresa; Gowland, M. Hazel; Egmose, Britt; Knibb, Rebecca; et al.
Abstract: Introduction: Adolescence is a critical stage of rapid biological, emotional and social change and development. Adolescents and young adults (AYA) with asthma and allergies need to develop the knowledge and skills to self‐manage their health independently. Healthcare professionals (HCP), parents and their wider network play an essential role in supporting AYA in this process. Previous work showed significant limitations in transition care across Europe. In 2020, the first evidence‐based guideline on effective transition for AYA with asthma and allergies was published by EAACI. Aim: We herein summarize practical resources to support this guideline's implementation in clinical practice. Methods: For this purpose, multi‐stakeholder Task Force members searched for resources in peer review journals and grey literature. These resources were included if relevant and of good quality and were pragmatically rated for their evidence‐basis and user friendliness. Results: Resources identified covered a range of topics and targeted healthcare professionals, AYA, parents/carers, schools, workplace and wider community. Most resources were in English, web‐based and had limited evidence‐basis. Conclusions: This position paper provides a valuable selection of practical resources for all stakeholders to support effective transitional care for AYA with asthma and allergies. Future research should focus on developing validated, patient‐centred tools to further assist evidence‐based transition care. Abstract :